Islamic geometric patterns their historical development and traditional methods of construction - Bonner, Jay (Springer, 2017)
Islamic Geometric Patterns presents an in-depth examination of the polygonal technique, the primary method used in creating Islamic geometric patterns. The text details the methodology behind this dead art form, and presents historical evidence, both of which are vital to the ornamental tradition